Contractor Intention on Contractors’ All Risk Takaful Product in Malaysian Construction Industry - Mohd Azizi Ibrahim; Alias Mat Nor; Raja Rizal Iskandar Raja Hisham (Universitas Syiah Kuala, 2021)
Objective – Contractors’ All Risks (CAR) Takaful is completely different from CAR conventional insurance. CAR conventional insurance involves elements of usury (riba), gambling (maysir) and uncertainty (gharar) in their resources and operations which is prohibited by Shari’ah. This paper aims to investigate the relationship between attitude, awareness, understanding, religiosity, subjective norm, service quality and role of agents with contractor’s intention in choosing CAR Takaful products based on theory of planned behaviour (TPB). In addition, this paper aims to address the most influential factors that affect contractor’s intention in choosing CAR Takaful products. Design/methodology – Using primary data collection method, 421 questionnaires were distributed to target respondents comprising Bumiputera contractors in Malaysia except for Sabah and Sarawak, who are registered with CIDB from grade G1 to grade G7 and also a member of Persatuan Kontraktor Melayu Malaysia (PKMM). The data were analysed using Statistical Package for the Social Sciences (SPSS) software version 25. Results – This study's results reveal a significant relationship between attitude, awareness, understanding, religiosity, subjective norm, service quality, and role of agents with contractor’s intention in choosing CAR Takaful product. In addition, this research also verifies that attitude is the most important factor that affects contractor’s intention in choosing CAR Takaful products. Contribution – This paper will bring significant benefits to the Takaful operators and Takaful agents in Malaysia to formulate additional strategies, policies and service quality to attract Bumiputera contractors to choose CAR Takaful product.